A STRUCTURAL-GEODYNAMIC FACTOR IN THE DISTRIBUTION OF GOLD MINERALIZATION IN SOUTHERN PRIMORYE - Utkin V.P.; Mitrokhin A.N.; Nevolin P.L.; Sayadyan G.R.; Sorokin B.K. (My University, 2004)
The constructed geologic-structural map is presented, in which one of main structures are open north-north-western fractures grouped in shear zones. The shear zones (which were especially studied) are characterized by the complex of structural and geodynamic factors (plutonic steeply dipping earth crust fractures possessing the dynamic effect of accelerated mineral-formation and substance remobilization, enhanced permeability for ore-bearing fluids and local ore-concentrating structures), which determined their dominating role in distribution of gold mineralization within Southern Primor'e.